Aplikasi Kolom Kapur Untuk Mengurangi Pengembangan Tanah Ekspansif Di Desa Pengengat Kecamatan Pujut Kabupaten Lombok Tengah - Muhajirah Muhajirah; Didi S Agustawijaya; Ismail H M; Shofia R (Universitas Mataram, 2020)
The growing population has an impact on the increasing need for housing. A comfortable house can be made if the ground is fine. Pengengat Village in Pujut District has expansive soil which has high swelling-shrinkage properties. This activity aims to provide an understanding of the characteristics of expansive soil and how to improve it. This activity is divided into three stages, including: 1) site survey, 2) counseling, and 3) creating a lime column model. The survey results show that people in Pengengat village do not understand the characteristics of expansive soil and they also do not know how to improve the soil phenomenon. The floors and walls of the house were cracked and some were split. Poor drainage conditions also contributed to the damage to their homes. After carrying out these activities, the residents began to understand the characteristics of the expansive soil and how to improve it. We make three lime columns with a diameter of 25 cm and a depth of 75 cm. The distance between the lime columns is 1 m. For evaluation purposes, we take soil samples from each hole, the soil samples will be tested to determine the level of swelling